The effect of perceived overqualification on relative deprivation: The moderating role of organisational silence - Çalışkan, Serkan; Polat, Eray; Esen, Ozan (ACC Publishing, 2025)
This study aims to investigate the perceptions of overqualification, relative deprivation, and organisational silence among gastronomy teachers employed in project schools established to enhance sector-school-student collaboration in Türkiye, and to examine the relationships among these perceptions. More specifically, the study will examine the effect of perceived overqualification on relative deprivation and the moderating role of organisational silence. To test the research hypotheses, a survey was conducted, and data were collected from 204 teachers. The primary effect was evaluated using simple linear regression analysis, while the PROCESS Macro was employed to assess the moderating effect. The influence of the interaction term was investigated with the Johnson-Neyman technique. The findings suggest that teachers who perceive themselves as overqualified tend to experience greater feelings of professional inadequacy. Conversely, this positive relationship intensifies as the perception of organisational silence diminishes. The study presents several recommendations for future research and practice. This study has the potential to establish a foundation for research into the relationships among perceived overqualification, relative deprivation, and organisational silence. Moreover, this study makes a contribution to the existing body of knowledge examining the effects of overqualification on person-centred outcomes.